The Relationship between Motivation, Satisfaction, and Organizational commitment among Scout volunteers in East Kalimantan, Indonesia - Yeni Rahmawati; Norhasni Zainal Ibiddin; Khusnul Khatimah (Universitas Muhammadiyah Kalimantan Timur, 2019)
The existence of volunteerism could be observed from several aspects in various communities as it is functioned as presented action with intention to help others and expect less material compensation or monetary advantages. Volunteers working under organizational context rather than working alone, they provide two services namely service for the society. this study has several emphasizes that arranged into several objectives namely; to determine the level of motivation, satisfaction, and organizational commitment, to determine the relationship between motivation and organizational commitment, to determine the relationship between satisfaction and organizational commitment, to determine the relationship among dimension and organizational commitment, to determine the best predictor dimension for organizational commitment. The present study is using quantitative research design, therefore it used descriptive as well as inferential statistic to analyze the data. According to the findings, regression model fit the data (F=10.280, p<.05). Based on the interpretation on the value, it could be decided that only understanding dimension (t= 2.531, p<.05) had significant contribution to the organizational commitment among scout volunteer in East Kalimantan.